Hybrid sensor fusion for unmanned ground vehicle - Guan, Mingyang (Nanyang Technological University, 2020)
The unmanned ground vehicles (UGVs) have been applied to execute many important tasks in the real world scenarios such as surveillance, exploring the hazard environment and autonomous transportation. The UGV is a complex system as it is integrated by several challenge technologies, such as simultaneously localization and mapping (SLAM), collision-free navigation, and robotic perception. Generally, the navigation and control of UGVs in the Global Positioning System (GPS) denied environment (i.e., indoor scenario) are critically dependent on the SLAM system which provides localization service for UGVs, while the robotic perception endows UGVs the ability of understanding their surrounding environments, such as continuously tracking the moving obstacles and then filtering them out in the localization process. In this thesis, we concentrate on the two topics involving autonomously robotic systems, say SLAM and visual object tracking.